Answer:
y=-4/3x-9
=
−
4
3
x
−
9
Step-by-step explanation:
First we need to get the slope of the perpendicular line
The slope of a perpendicular line is equal to the negative inverse of the slope of the given line
y
=
m
x
+
b
y
=
3
4
x
−
2
⇒
m
=
3
4
m
'
=
−
1
m
⇒
m
'
=
−
1
3
4
⇒
m
'
=
−
4
3
Now that we have the slope, we need to find the y-intercept.
To find the y-intercept, we need to plug-in values of
x
and
y
that the line passes through
y
'
=
m
'
x
'
+
b
⇒
y
'
=
−
4
3
x
'
+
b
⇒
7
=
−
4
3
(
−
12
)
+
b
⇒
7
=
16
+
b
⇒
b
=
−
9
Therefore, the equation of the line is
y
=
−
4
3
x
−
9
Answer:
6.7
Step-by-step explanation:
Answer:
E
Step-by-step explanation:
Its simple
Step-by-step explanation:
f(g(x))
= f(4x)
= (4x) - 3. (A)